Clinical, haematological, and biochemical profile of HIV patient co-infected with hepatitis B and /or C - Suman, Sonu (International Journal of Research in Medical Sciences, 2020)
Background: Human immunodeficiency virus (HIV) positive population is at higher risk of getting infected with hepatitis B virus (HBV) or hepatitis C virus (HCV) or both. Co-infection with HBV/HCV may possibly complicate the clinical course of HIV in infected patients. Aim and objectives of the study were intended to determine clinical, haematological and biochemical profile of HIV patients co infected with hepatitis B and/or C. Methods: All consecutive patients presented with HIV infection who were coinfected with either Hepatitis B, C or both presenting to immunodeficiency or Gastroenterology OPD Base Hospital Delhi, were included in the study. It was a prospective, observational study. Results: HIV impacts the progression of HCV and increases the likelihood of subsequent liver damage as it is apparent in study by significant raised liver enzymes and hypoalbuminemia in HIV-HCV co infection compare to HIV–HBV. Conclusions: These coinfections are more common in younger and lesser educated people. Biochemical parameters could serve as pointers for early detection of liver disease as result of hepatitis co infections in HIV patients. Prompt diagnosis of HCV and HBV co-infection in HIV patients has both individual and public health benefits.